ANALYSIS OF EFFECT OF INTERESTS READ, STUDY MOTIVATION AND COUNSELING ACADEMICTOSTUDENT ACHIEVEMENT INDEX EDUCATION OF MECHANICAL ENGINEERING OF PALANGKARAYA UNIVERSITY - Whendy Trissan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
Some indicators are often installed to suggest the quality of graduates is (1) GPA; (2) Duration of Study and; (3) The predicate graduation girded. It is part of the learning achievements of students to see the level of success in achieving the learning objectives specified in the curriculum of Mechanical Engineering Education. The curriculum is a program designed to achieve educational goals. This study is intent of determine the relationship existing curriculum in Mechanical Engineering Education with a GPA of students who have graduated and longer studies are pursued. The method used to knowingrelationship curriculum, GPA and long study used a qualitative approach. This type of research is a case study. The case studies presented in descriptive form. The presence of researchers in the field to act as a participant observer